URGENCY OF ORGANIZATIONAL CHANGE MANAGEMENT IN EDUCATIONAL INSTITUTIONS - Pramitha, Devi (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
Various efforts and approaches have been taken to solve problems arising from changes. Changes can occur because of reasons that originate from within or outside the organization. However, the change itself has benefits for the survival of an organization, without any change, it can be ascertained that the age of the organization will not last long. The basic concept of change management is to implement a strategy and analyze a change that might be experienced by the company or an educational institution due to the formulation of the strategy agreed upon in the previous stage. This change aims to provide a clear and detailed idea of how much an educational institution must change and succeed in implementing a strategy.